Validity of Teaching Materials for Writing Poetry Based on Creative Techniques in Elementary Schools - Habibi, M; Chandra, Chandra; Mahyuddin, Ritawati; Hendri, S (Universitas Pendidikan Indonesia, 2018)
One form of literary literacy in elementary schools is that students are able to write poetry. But in reality, students tend to have difficulty making poetry with certain themes. The reason is because teaching materials used were not able to lead students to carry out poetry writing activities well. Therefore, this study aims to develop teaching materials for writing poetry that is valid. The use of various creative techniques is expected to help students in expressing their ideas and imagination into verses of poetry. The research design uses Research and Development with the ADDIE development model. This model consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data to determine the level of validity of instructional materials obtained by expert validation and practitioner validation. Validation aspects of teaching materials include: (1) content feasibility aspects, (2) language aspects, (3) presentation aspects, and (4) graphical aspects. Research findings show that teaching materials for poetry writing based on creative techniques are declared valid with an average score of 3.59. Specifically, the scores obtained for each aspect are: (1) content feasibility 3.59, (2) language 3.45, (3) presentation 3.61, and (4) graphical 3.68.